The interactions of diet-induced obesity and organophosphate flame retardant exposure on energy homeostasis in adult male and female mice. Issue 11 (17th June 2020) - Vail, Gwyndolin M.; Walley, Sabrina N.; Yasrebi, Ali; Maeng, Angela; Conde, Kristie M.; Roepke, Troy A.
ABSTRACT: Previously, sex-dependent alterations in energy homeostasis were reported in adult mice fed a standard chow attributed to exposure to a mixture of organophosphate flame retardants (OPFRs) via estrogen receptors (ERα). In this study, adult male and female mice (C57BL/6J; Taconic) were treated with the same mixture of OPFRs (1 mg/kg each of tricresyl phosphate (TCP), triphenyl phosphate (TPP), and tris(1-3-dichloro-2propyl)phosphate (TDCPP)) for 7 weeks on a low-fat diet (LFD, 10% kcal fat) or a high fat (HFD, 45% kcal fat) in a diet-induced obesity model. Consistent with our previous observations, OPFRs altered weight gain in males, differentially with diet, while females remained unaffected. OPFR treatment also revealed sex-dependent perturbations in metabolic activity. During the night (approximately 0100–0400 hr), males exhibited elevated activity and oxygen consumption, while in females these parameters were decreased, irrespective of diet. OPFR disrupted feeding behavior and abolished diurnal water intake patterns in females while increasing nighttime fluid consumption in males. Despite no marked effect of OPFRs on glucose or insulin tolerance, OPFR treatment altered circulating insulin and leptin in females and ghrelin in males. Data indicate that adult OPFR exposure might influence, and perhaps exacerbate, the effects of diet-induced obesity in adult mice by altering activity, ingestive behavior, and metabolism.